Recurrent laryngeal papillomatosis: successful treatment with human papillomavirus vaccination - Mudry, Peter; Vavrina, Martin; Mazanek, Pavel; Machalova, Michaela; Litzman, Jiri; Sterba, Jaroslav (Archives of disease in childhood, 2011)
The authors describe the case of a 5-year-old girl with recurrent laryngeal papillomatosis (RLP) due to human papillomavirus (HPV) type 11, who required frequent surgical treatment. Complete recovery occurred after HPV vaccination (Gardasil). Confirmed remission of RLP has continued during the 17 months of follow-up since vaccination. The authors conclude that HPV vaccination may represent a new therapeutic option in this situation.
Keywords: Laryngeal Neoplasms; Child, Preschool; vakcíny proti papilomavirům; Papillomavirus Vaccines; lidé; nádory hrtanu; Papilloma; Follow-Up Studies; předškolní dítě; Human Papillomavirus Recombinant Vaccine Quadrivalent, Types 6, 11, 16, 18; sekundární prevence; Humans; Secondary Prevention; následné studie; papilom; rekombinantní kvadrivalentní vakcína proti lidskému papilomaviru typu 6, 11, 16, 18; ženské pohlaví; Female